#### Answer

$25i$

#### Work Step by Step

$i(3 + 4i)(3 - 4i) = i(9 +12i - 12i - 16i^2) = i(9 -16 (-1)) = 25i$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$25i$

$i(3 + 4i)(3 - 4i) = i(9 +12i - 12i - 16i^2) = i(9 -16 (-1)) = 25i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.